Analisis Tantangan Persaingan Usaha dan Strategi Promosi pada Umkm Sembako Rafa di Maguwoharjo, Depok Sleman Yogyakarta - Merllia Putri Zahwa; Hasim As’ari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The rapid growth of modern retail in urban areas poses a serious challenge to the sustainability of food-based Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the business competition challenges and promotional strategies implemented by UMKM Sembako Rafa in Maguwoharjo, Depok, Sleman, Yogyakarta. A descriptive qualitative method with a case study approach was employed, using in-depth interviews, direct observation, and documentation for data collection. The results indicate that the primary business competition challenges faced by UMKM Sembako Rafa stem from external competitors, which periodically trigger a fluctuating phase of low customer traffic. Nevertheless, the daily income levels remain relatively stable. In managing its marketing aspects, UMKM Sembako Rafa opts for a defensive promotional strategy that focuses entirely on conventional customer retention and loyalty rather than aggressive mass promotion. Furthermore, as an adaptation to digital opportunities, the owner effectively diversifies personal income by actively participating as an online product affiliate. The combination of a loyal regular customer base and digital side-income flexibility serves as a crucial instrument in maintaining the resilience of this micro-business.